2018
DOI: 10.20884/1.jm.2018.13.1.417
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract of Tithonia diversifolia (Hemsley) A Gray Standardized Ameliorates Hyperglycemia, Polyphagia, and Weight Loss in Diabetic Rats

Abstract: Diabetes mellitus is a state of chronic hyperglycemia which causes various complications. Traditionally, The Tithonia diversifolia (Hemsley) A Gray leaf has long been used for the treatment of diabetes. The aim of this study is to investigate the effect of the T. diversifolia leaf on blood glucose, polyphagia, and weight loss in a diabetic rat model. Rats were made diabetic with intraperitonial injection of Nicotinamide and Streptozotocin and divided into 5 groups. Group 1 were healthy rats, group 2 were diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…10 Tithonia diversifolia was demonstrated to reduce the blood sugar levels of diabetic rats. 11,12 In a previous study, TDL extract at doses of 25 mg/kg BW, 50 mg/kg BW, and 100 mg/kg BW significantly reduce blood sugar levels.12 However, in this study, with a similar treatment, TDL extract administration at a 25 mg/kg BW dose was insufficient to increase the NO level, as shown in Table 1. Meanwhile, K.4 and K.5 groups demonstrated an increase in NO levels compared to the diabetic control group.…”
Section: Discussionmentioning
confidence: 54%
“…10 Tithonia diversifolia was demonstrated to reduce the blood sugar levels of diabetic rats. 11,12 In a previous study, TDL extract at doses of 25 mg/kg BW, 50 mg/kg BW, and 100 mg/kg BW significantly reduce blood sugar levels.12 However, in this study, with a similar treatment, TDL extract administration at a 25 mg/kg BW dose was insufficient to increase the NO level, as shown in Table 1. Meanwhile, K.4 and K.5 groups demonstrated an increase in NO levels compared to the diabetic control group.…”
Section: Discussionmentioning
confidence: 54%
“…Polyphagia results from cells experiencing a lack of energy because glucoe cannot be absorbed into the cell. Fauziah et al (2018) explained when the cells deficient glucose will activate the hunger center located in the hypothalamus section so increase food intake. When the cells in the condition lack of energy, adipose is presumably because the dose used in the study is lower.…”
Section: Results and Disscusionsmentioning
confidence: 99%
“…Sesquiterpen lactone compounds and tagitinin A can increase peroxisome proliferator-activated recep-tors (PPARs) ϒ activity so as to increase insulin sensitivity (Lin, 2012). PPARs ϒ activation can increased the expression of a number of genes associated with glucose metabolism and regulated insulin transcription in pancreatic β cells (Fauziah et al, 2018). Increasing body weight in glibenclamide treatments was thought to be a side effect of the ability to reduce blood glucose levels.…”
Section: Results and Disscusionsmentioning
confidence: 99%
“…In our previous study, T. diversifolia extract was shown to exert anti-hyperglycaemic effects ( 6 ). Therefore, in the present study, we improved the quality and reproducibility of the extract through a more complete standardisation process that included several specific and non-specific parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Tithonia diversifolia (Hemsley) A Gray extract antihyperglycaemic activity that is beneficial for the treatment of T2DM ( 6 ). In vitro studies have demonstrated the ability of T. diversifolia to act as a peroxisome proliferator activator receptor (PPARα/γ) agonist ( 7 ), which increases 5’AMP-activated protein kinase (AMPK) phosphorylation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%